Highly-efficient production of spherical co-agglomerates of drugs via an organic solvent-free process and a mechanism study. Issue 7 (22nd March 2021) - Sun, Mengmeng; Liu, Yanbo; Yan, Hui; Chen, Mingyang; Gong, Junbo
Abstract : A highly-efficient drug co-agglomeration technique was developed, overcoming the limitations of the current methods where biohazardous solvents and complex equipment were involved. Abstract : This work aims at developing a green and highly-efficient technique, which enables co-crystallization and co-agglomeration of drugs, or the crystallization of one drug and simultaneous agglomeration with another drug, in pure water taking advantage of oiling-out. By establishing the phase diagram and making use of the oil droplets formed in an oiling-out system, spherical co-agglomerates containing desired ratios of drugs, ibuprofen (IBU) with a second active pharmaceutical ingredient (API), including l -menthol (MT), praziquantel (PZQ), rivaroxaban (RXB) and lenalidomide (LDM), were successfully prepared, simply relying on a heating–quenching operation. Forming processes of the spherical co-agglomerates involved two kinds of mechanisms: co-oiling-out and single-oiling-out mechanisms, making the oiling-out co-agglomeration (OOCA) technique suitable for a wide range of applications in pharmaceuticals. Particularly, the co-oiling-out mechanism, which was proposed and designed, for the first time in this work based on ternary phase diagrams of (API1 –API2 –water), uniform oil droplets of two APIs were generated, guaranteeing a high degree of content uniformity in the co-agglomerate products. The OOCA technique developed in this work can not only incorporate crystallization and granulation into one unit operation, but also help in achieving drug combination (polypills). An effective screening strategy for drugs applicable to the OOCA technique was established by simulation and computation, greatly reducing the utilization of chemical substances and helping save time in the promotion process of OOCA.